Reconstruction of Equitable Customary Land Management To Improve The Investment Climate in Jayapura Regency - polontoh, Herry M; Mulyadi, Dudi; Yanuaria, Tri; Hamonangan, Sobardo (PT. Anagata Sembagi Education, 2025)
Customary land management in Jayapura Regency has a strategic role in encouraging regional economic growth through improving the investment climate. However, management practices have often caused problems such as land conflicts, legal uncertainty, and low participation of indigenous peoples in decision-making. This condition hinders investors from investing their capital optimally. This research aims to formulate a model for reconstruction of customary land management that is fair, provides legal certainty, and facilitates synergy between indigenous peoples, local governments, and investors. The research method used is a qualitative approach with a descriptive-analytical design. Data was obtained through in-depth interviews with traditional leaders, local government officials, investors, and academics, as well as through the study of relevant laws and regulations. The analysis was carried out using the Miles & Huberman interactive model technique, including data reduction, data presentation, and conclusion drawn. The results of the study show that equitable management of customary land requires formal recognition of customary rights, the existence of a clear written agreement mechanism between customary rights owners and investors, and the existence of permanent mediation institutions to resolve disputes quickly. The implementation of this reconstruction model has been proven to increase legal certainty, reduce potential conflicts, and encourage increased investment interest in Jayapura Regency.